2013
DOI: 10.4038/seajme.v7i1.147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of case-based learning as an adjunct to traditional teaching learning methods in Physiology

Abstract: Introduction: The present study was undertaken with the objective to assess the efficacy of clinical case history based modular teaching learning method on the performance of undergraduate medical students as an adjunct to the traditional teaching methods in physiology. Materials and Methods: The present study was performed on first professional MBBS students of two consecutive batches of Nilratan Sircar Medical College, Kolkata. After the first semester examination was taken, a significant deviation in teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
1
7
1
1
Order By: Relevance
“…The present study findings are also consistent with Rehman R [12] who found majority of medical students were able to understand core content of physiology and co relate it with pathological aspects to identify diseases by casebased learning. Our study concurs with the finding of Panja et al [13] where CBL was applied on two batches, and was found to impart significant difference in students' performance. Study done by Diwan et al [14] concluded that CBL when used as an adjunct to didactic lectures strengthens traditional teaching through active learning.…”
Section: Discussionsupporting
confidence: 92%
“…The present study findings are also consistent with Rehman R [12] who found majority of medical students were able to understand core content of physiology and co relate it with pathological aspects to identify diseases by casebased learning. Our study concurs with the finding of Panja et al [13] where CBL was applied on two batches, and was found to impart significant difference in students' performance. Study done by Diwan et al [14] concluded that CBL when used as an adjunct to didactic lectures strengthens traditional teaching through active learning.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we did observe a tendency for CB teaching methods to improve student performance on multiple-choice questions. The observed tendency may be explained by the findings from Panja et al (2013) and Bi et al (2019) , whereby CB teaching methods improved student performance on CB and non-CB assessments. Case-based teaching methods have been associated with a deeper understanding and higher-level learning of the content compared with LB teaching ( Panja et al, 2013 ; Bi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…The observed tendency may be explained by the findings from Panja et al (2013) and Bi et al (2019) , whereby CB teaching methods improved student performance on CB and non-CB assessments. Case-based teaching methods have been associated with a deeper understanding and higher-level learning of the content compared with LB teaching ( Panja et al, 2013 ; Bi et al, 2019 ). In a meta-analysis, Bredow et al (2021) reported a consistent finding in existing research that student performance improved when active learning (e.g., CB) was used in addition to lecture.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations